Predicting Unsteady Loads in Marine Propulsor Crashback Using Large Eddy Simulation - Hyunchul Jang; Aman Verma; Krishnan Mahesh (International Journal of Rotating Machinery)
Propulsor crashback is an off-design operating condition where a propulsor rotates in the reverse direction to yield negative thrust. Crashback is characterized by the interaction of the free stream with the reverse flow generated by propulsor rotation. This causes a highly unsteady vortex ring which leads to flow separation and unsteady forces and moments on the blades. Large eddy simulation (LES) is performed for marine propulsors in crashback for various configurations and advance ratios and validated against experiments. The predictive capability of LES as a tool for propulsor crashback is demonstrated on an open propulsor, open propulsor with a submarine hull, and ducted propulsor with and without stator blades. LES is in good agreement with experiments for the mean and RMS levels, and spectra of the unsteady loads on the propulsors.